2023
DOI: 10.3390/jfb14080409
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Pectin–Alginate Hydrogels for Improving Vascularization and Adipogenesis of Human Fat Graft

Abstract: Autologous fat grafting (AFG) is the most prevailing tool for soft tissue regeneration in clinics, although efficiency is limited to unpredictable volume resorption due to poor vascularization and eventual necrosis. This study sought to improve the AFG efficiency using a hydrogel as a carrier for human fat graft (F) with and without platelet-rich plasma (PRP). PRP is clinically well known for the local release of several endogenous growth factors and has been in clinical use already. A human-fat-graft-encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Third, several tissue engineering strategies have been developed to enhance fat graft survival and therefore allow for the maintenance of tissue volume. These include the use of natural biomaterials [35] and/or growth factors [36]. Although very attractive, these approaches are often difficult to integrate into clinical practice due to regulatory constraints and potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…Third, several tissue engineering strategies have been developed to enhance fat graft survival and therefore allow for the maintenance of tissue volume. These include the use of natural biomaterials [35] and/or growth factors [36]. Although very attractive, these approaches are often difficult to integrate into clinical practice due to regulatory constraints and potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented in figure 8 offer empirical evidence of the IPN scaffolds' enhanced ability to stimulate vascularization compared to controls, marking a significant step forward in improving artificial bone grafts and advancing bone tissue engineering. Janarthanan et al previously demonstrated pectin's significant effects on endothelial cells, promoting vascularization [94]. Flournoy et al's research further underscores the role of mechanobiological factors, like substrate stiffness and geometry, in regulating angiogenesis [95].…”
Section: Angiogenesis Potential Of the Ipn Scaffoldmentioning
confidence: 98%